A safety evaluation of aripiprazole in the treatment of schizophrenia. Issue 12 (1st December 2020) - Preda, Adrian; Shapiro, Bryan B.
ABSTRACT: Introduction: Aripiprazole is a third generation antipsychotic approved by the US Food and Drug Administration (FDA) for the treatment of schizophrenia. Aripiprazole is available as oral and long-acting injectable (LAI) depot formulations, with a unique mechanism of action comprising partial D2 and serotonin 5-HT1A agonism and antagonism at serotonin 5-HT2A receptors. Areas covered: We review short-and-long-term clinical trials, meta-analyses of clinical trials and product information pertaining to the safety and efficacy of aripiprazole in adults with schizophrenia. Formulations of aripiprazole reviewed include oral aripiprazole, Aripiprazole monohydrate LAI (Abilify Maintena©) and Aripiprazole lauroxil LAI (Aristada©). Clinical studies and product information were collected from PubMed, Psychinfo, Embase, and other web sources. Expert opinion: Aripiprazole is a generally well-tolerated third-generation antipsychotic with low rates of motor side effects and metabolic adverse effects that occur commonly with several alternative antipsychotics. Akathisia and tremor appear to occur at higher rates with aripiprazole compared to placebo but are still generally uncommon with incidences of 10–11% or less. Uniquely, aripiprazole treatment is associated with reduced serum prolactin levels and QTc interval. A variety of LAI options with dosing intervals as infrequent as every 8 weeks provide a compelling reason to select aripiprazole in patients with limited oral treatment adherence.